2010
DOI: 10.1128/jcm.00736-10
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Transported Dry and Wet Cervical Exfoliated Samples for Detection of Human Papillomavirus Infection

Abstract: We determined the feasibility of human papillomavirus (HPV) detection in cervical exfoliated cells collected as dry swab samples. Both dry cervical swab and specimen transport medium (STM) cervical swab samples were collected from 135 patients attending either colposcopy or women's clinics in Guayaquil, Ecuador, who had a cytology diagnosis within 6 months. HPV was detected by dot blot hybridization and genotyped by the liquid bead microarray assay (LBMA). Overall, 23.1% of dry samples were positive for any hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
25
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 17 publications
6
25
1
Order By: Relevance
“…Feng et al (2010) observed substantial agreement between high-risk HPV (for positive agreement k 0.61) cervical samples, collected from 135 women (mean age 38) attending colposcopy or women's clinics in Ecuador, that were transported dry and wet. Time between sample collection and HPV testing was longer in the study of Feng et al (2010) because samples were refrigerated for up to 6 months before they were shipped from Ecuador to Washington State for HPV testing. Differences in age, HPV prevalence and sampling site between Feng et al (2010) and the present study could also account for differences in observed agreement.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Feng et al (2010) observed substantial agreement between high-risk HPV (for positive agreement k 0.61) cervical samples, collected from 135 women (mean age 38) attending colposcopy or women's clinics in Ecuador, that were transported dry and wet. Time between sample collection and HPV testing was longer in the study of Feng et al (2010) because samples were refrigerated for up to 6 months before they were shipped from Ecuador to Washington State for HPV testing. Differences in age, HPV prevalence and sampling site between Feng et al (2010) and the present study could also account for differences in observed agreement.…”
Section: Discussionmentioning
confidence: 99%
“…Infections detected in younger women may be more likely to reflect newer HPV infections with higher viral loads (Winer et al, 2007) and because higher viral loads increase the likelihood of detecting the virus in a sample (Winer et al, 2007), agreement between samples could be enhanced compared to infections with lower viral loads. Feng et al (2010) compared clinician-collected cervical samples, while our study compared self-collected vaginal samples. We previously demonstrated that greater numbers of HPV infections were detected in paired vulvovaginal versus cervical samples, possibly due to the larger surface area of the vagina compared to the cervix (Winer et al, 2003(Winer et al, , 2007.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations